Livestock Groups in Dolokgede Village: Socioeconomic Profile and Local Resource Utilization - Diony, Diony Ahlul Fikri; Huda, Asri Nurul; Mashudi, Mashudi; Susilawati, Trinil; Yekti, Aulia Puspita Anugra; Febrianto, Nanang (CV. Komunitas Dunia Peternakan, 2026)
Small-scale beef cattle farming systems play an important role in rural livelihoods in developing countries. However, comprehensive analysis that integrates the socioeconomic characteristics of farmers with resource utilization patterns is still limited. This study aims to evaluate the socio-economic characteristics of farmers and resource utilization patterns in the beef cattle business in Dolokgede Village, Tambakrejo District, Bojonegoro Regency. Based on the results of the evaluation, it can determine and identify the potential for the development of livestock businesses and in this region. Quantitative descriptive research was carried out using a direct survey method on farmers through questionnaires and environmental analysis. The sample was determined by the Slovin formula with an error rate of 10%, resulting in 29 respondents who were selected by simple random sampling. Data were collected through structured interviews and analyzed using descriptive statistics. Farmers are dominated by the productive age of 31-60 years (72.41%) with the majority of elementary education (75.86%). The selection of 2-5 cattle dominates (65.52%) with the Peranakan Ongole type. The use of feed is integrated with the agricultural system through rice straw (96.55%) and corn waste (93.10%). Feed costs account for more than 60% of the total cost of production, but the R/C ratio shows a value above 1, indicating the economic viability of the business. The beef cattle business in Dolokgede Village has the potential for development through stronger plant-livestock integration, improved feed technology, and institutional support for market access and financing.